2023
DOI: 10.7150/thno.83914
|View full text |Cite
|
Sign up to set email alerts
|

PCSK9 attenuates efferocytosis in endothelial cells and promotes vascular aging

Abstract: Aims: Proprotein convertase subtilisin/kexin type 9 (PCSK9) is a serine protease that binds to low-density lipoprotein receptors. Efferocytosis is the process by which phagocytes remove apoptotic cells. Both PCSK9 and efferocytosis play important roles in regulating redox biology and inflammation, the key factors contributing to vascular aging. This study was designed to investigate the impact of PCSK9 on efferocytosis in endothelial cells (ECs) and its implications in vascular aging. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…[ 4 ] ANXA1 expression was consistently reduced in both the replicative senescence model and under chronic TNF‐α treatment to simulate the inflammaging state in vitro. However, in recent years, except for HUVECs, more kinds of endothelial cells need to be performed since several kinds of endothelial cells, like cultured endothelial cells from rat aorta, human aorta, [ 37 ] and bovine pulmonary artery, [ 38 ] can simulate endothelial cells status. In recent years, various studies focused on vascular calcification and vascular aging used these cells for investigation.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 ] ANXA1 expression was consistently reduced in both the replicative senescence model and under chronic TNF‐α treatment to simulate the inflammaging state in vitro. However, in recent years, except for HUVECs, more kinds of endothelial cells need to be performed since several kinds of endothelial cells, like cultured endothelial cells from rat aorta, human aorta, [ 37 ] and bovine pulmonary artery, [ 38 ] can simulate endothelial cells status. In recent years, various studies focused on vascular calcification and vascular aging used these cells for investigation.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some limitations in our current study. First, it has been shown that MerTK is expressed in macrophages 39 , vascular ECs 8 , 27 , and vascular smooth muscle cells (SMCs) 40 .…”
Section: Discussionmentioning
confidence: 99%
“…We recently reported that primary aortic ECs have high ability to perform efferocytosis and EC efferocytosis plays important roles in vascular aging 8 . However, the previous studies did not show the direct link between blood flow patterns and EC efferocytosis as well as the interaction between blood flow patterns and MerTK expression.…”
Section: Introductionmentioning
confidence: 99%